Pengaruh Hypnobirthing Terhadap Tingkat Nyeri Dan Kemajuan Persalinan Pada Ibu Bersalin Di Bpm Kota Cimahi - Indria Astuti; Noviyanti Noviyanti (AIPKIND (Asosiasi Pendidikan Kebidanan Indonesia), 2015)
Approximately 90% of causes of maternal deaths occur during delivery due to obstetric complications. One of the complications is prolonged labor caused by inadequate contractions. One method to maintain the uterine contractions is with hypnobirthing. The objective of this research was to determine the effects of hypnobirthing on the level of pain and the progress of labor. This was a true experiment with a posttest only control design. The population was women delivering at BPM at the Cimahi amounting to 30 respondents. The sampling technique used accidental sampling based on research criteria. Data collection method used observation sheets and partograph. The data were then analyzed using bivariate analysis with T-test independent. The results showed that the p-value obtained was 0.001 and 0.038, respectively, meaning that there was a significant relationship between hypnobirthing and decreased pain intensity and between hypnobirthing and the progress of labor.